Taxation : an interdisciplinary approach to research - Lamb, Margaret (Margaret Anne); Lymer, Andrew; Freedman, Judith; James, Simon (Oxford University Press, 2005)
The book offers an innovative introduction to tax research by combining commentary on disciplinary-based and interdisciplinary approaches. Its objective is to guide and encourage researchers how to produce taxation research that is rigorous and relevant. Effective approaches to research problem definition and research method choice are outlined by leading authors in their fields. The book provides suggestions of topics, readings, and approaches that are intended to help the new. researcher choose ways to begin their tax research. - ;Taxation involves complex questions of policy, law, and pract.